Clinical experience in appendiceal neuroendocrine neoplasms - Ozcelik, Caglar K.; Turanlı, Sevim; Bozdogan, Nazan; Dibekoglu, Cengiz (Contemporary Oncology/Współczesna Onkologia, 2015)
Aim of the study: To analyse the incidence of appendiceal neuroendocrine neoplasms in appendectomy specimens and establish the epidemiological and histopathological features, treatment, and clinical course. Material and methods: Between 2004 and 2013, 975 patients who underwent appendectomy in Ankara Oncology Education and Research Hospital were retrospectively analysed. Results: Neuroendocrine neoplasm was detected in the nine of 975 (0.9%) patients. Neuroendocrine neoplasms were diagnosed in eight patients by appendectomy, which was performed because of the prediagnosis of acute appendicitis, and in one patient by the suspicious mass detection during surgical procedures that were done in the appendix for a different reason. Eight of the patients’ tumours were in the tip of the appendix, and one of the patients’ tumours was at the base of appendix. Tumour size in 77.8% of patients was equal or less than 1 cm, in 22.2% patients it was 1–2 cm. There was tumour invasion in the muscularis propria layer in four patients, in the serosa layer in three patients, and in the deep mesoappendix in two patients. Patients were followed for a median of 78 months. In the follow-up of patients who were operated because of colon cancer, metachronous colon tumour evolved. This patient died due to progressive disease. Other patients are still disease-free. Conclusions : The diagnosis of neuroendocrine neoplasm is often incidentally done after appendectomy. Tumour size is important in determining the extent of disease and in the selection of the surgical method during operation.